Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/sode.12256
|View full text |Cite
|
Sign up to set email alerts
|

Children's attentional breadth around their mother: Comparing stimulus‐driven vs. cognitively controlled processes

Abstract: Attentional processes in children are tuned toward their mother. It is unclear whether this is a cognitively controlled or more automatic, stimulus-driven process. Therefore, 172 children (age 9-13) were assigned to either a cognitively controlled or a stimulus-driven task measuring the breadth of their attentional field around their mother.Results demonstrated a narrower field around the mother for children completing the more stimulus-driven task. Moreover, only for the stimulus-driven task, this effect was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(74 reference statements)
3
3
0
Order By: Relevance
“…In addition, the current results seem to indicate that children with greater attachment security are able to successfully regulate negative emotions independently of whether they approach or avoid mother. This finding is in line with accumulating evidence that, throughout middle childhood, more securely attached children become increasingly autonomous and can cope with mild levels of stress independently (Borelli, Somers, West, Coffey, & Shmueli-Goetz, 2016;Bosmans et al, 2017;Dujardin et al, 2015). Throughout development, children gradually shift from dyadic, caregiver-supported regulation to relatively independent self-regulation (Maunder & Hunter, 2001).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the current results seem to indicate that children with greater attachment security are able to successfully regulate negative emotions independently of whether they approach or avoid mother. This finding is in line with accumulating evidence that, throughout middle childhood, more securely attached children become increasingly autonomous and can cope with mild levels of stress independently (Borelli, Somers, West, Coffey, & Shmueli-Goetz, 2016;Bosmans et al, 2017;Dujardin et al, 2015). Throughout development, children gradually shift from dyadic, caregiver-supported regulation to relatively independent self-regulation (Maunder & Hunter, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Pictures of 10 different unfamiliar mothers were used to control for possible effects of attractiveness or resemblance to mother or others. All pictures were taken in front of a neutral background and all women were asked to display a neutral facial expression with closed lips, as has been done in prior research (e.g., Bosmans, De Raedt, & Braet, 2007;Bosmans, Rinck, et al, 2009;Bosmans et al, 2017), to reduce variability across photographs. To accommodate the zoom-function, seven sizes of each picture were created, with pixel sizes of 37 × 57, 58 × 88, 90 × 136, 140 × 210, 216 × 324, 333 × 499, and 513 × 768. Each picture was presented in size 140 × 210 pixels and decreased or increased in size in three steps.…”
Section: Approaching Versus Avoiding Mothermentioning
confidence: 99%
“…This protective effect of a broad attentional field for less distressed securely attached children can be understood from the healthy effect of increased autonomy development at this age (Bosmans & Kerns, 2015). This is in line with other research showing that secure attachment gets increasingly linked to a wider attentional field around the mother as children grow older (Bosmans et al, 2017) and that securely attached children more easily attentionally disengage from mother in favor of attentional exploration (Dujardin et al, 2015). So, a broader attentional field around the mother might be highly adaptive in service of autonomy development, but only if children are not exposed to higher levels of distress later in their development.…”
Section: Discussionsupporting
confidence: 82%
“…To measure children's attentional field around their mother, a picture of the mother together with a target stimulus are presented at a presentation time that prevents eye saccades (32 ms). This way, the breadth of the attentional field around the mother refers to the pre-attentive stages of information processing, more automatically triggered by the motivational or emotional relevance of the mother as a stimulus (Bosmans et al, 2017;Derryberry & Tucker, 1994).…”
Section: The Moderating Role Of Children's Attentional Breadth Aroundmentioning
confidence: 99%
“…Particularly in the context of middle childhood attachment, recent research would support this proposal. For example, Bosmans et al (2017) showed that children have an attentional preference for their mother, but whether this preference is adaptive or maladaptive depends on factors like children's stress and trust levels (e.g., . Children with more trust seem protected in stressful situations if they are more strongly focused on their mother, but the same attentional focus on mother becomes a liability if children lack trust (e.g, Bosmans et al, 2013).…”
mentioning
confidence: 99%